2022
DOI: 10.3389/fbioe.2022.979497
|View full text |Cite
|
Sign up to set email alerts
|

Function-based classification of hazardous biological sequences: Demonstration of a new paradigm for biohazard assessments

Abstract: Bioengineering applies analytical and engineering principles to identify functional biological building blocks for biotechnology applications. While these building blocks are leveraged to improve the human condition, the lack of simplistic, machine-readable definition of biohazards at the function level is creating a gap for biosafety practices. More specifically, traditional safety practices focus on the biohazards of known pathogens at the organism-level and may not accurately consider novel biodesigns with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 211 publications
0
4
0
Order By: Relevance
“…An accurate computational assessment of the infectiousness of a synthetic microbe is not currently possible nor is it likely to be in the next decade. We think our work and that of others can provide pointers for how such as assessment might be attempted ( Gemler et al, 2022 ; Godbold et al, 2022 ). Our criteria for functions of sequences of concern were described in our earlier publication and are available to the scientific community.…”
Section: Implications For Biosafety Biosecurity and Dual-use Research...mentioning
confidence: 89%
“…An accurate computational assessment of the infectiousness of a synthetic microbe is not currently possible nor is it likely to be in the next decade. We think our work and that of others can provide pointers for how such as assessment might be attempted ( Gemler et al, 2022 ; Godbold et al, 2022 ). Our criteria for functions of sequences of concern were described in our earlier publication and are available to the scientific community.…”
Section: Implications For Biosafety Biosecurity and Dual-use Research...mentioning
confidence: 89%
“…Recent work in our laboratory analyzing novel SARS-CoV-2 demonstrated that UltraSEQ could identify SARS-CoV-2 as a SARS-CoV-1-related virus (data not shown). Furthermore, analytical models built from hazardous function signals (using the methodology reported in our recent publication [ 8 ]) demonstrated that SARS-CoV-2 clusters with other SARS-CoVs with similar host ranges and human receptor types. Future work will expand on these advances and improve UltraSEQ’s ability to characterize features of emerging pathogens of clinical and research significance.…”
Section: Discussionmentioning
confidence: 99%
“…UniRef100 provides coverage across the tree of life (pathogens and nonpathogens) and provides the foundation for taxonomic calls in UltraSEQ. In addition, we used Battelle’s Sequence of Concern (SoC) protein database, described previously ( 8 ). This database contains ~12,300 manually selected publicly available UniProt protein sequences that have been curated based on functions such as enabling antibiotic resistance, immune evasion, toxicity, and/or other threatening functions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation